3(22)+3(4)=3(x)+3(6)

Simple and best practice solution for 3(22)+3(4)=3(x)+3(6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(22)+3(4)=3(x)+3(6) equation:


Simplifying
3(22) + 3(4) = 3(x) + 3(6)

Multiply 3 * 22
66 + 3(4) = 3(x) + 3(6)

Multiply 3 * 4
66 + 12 = 3(x) + 3(6)

Combine like terms: 66 + 12 = 78
78 = 3(x) + 3(6)

Multiply 3 * 6
78 = 3x + 18

Reorder the terms:
78 = 18 + 3x

Solving
78 = 18 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
78 + -3x = 18 + 3x + -3x

Combine like terms: 3x + -3x = 0
78 + -3x = 18 + 0
78 + -3x = 18

Add '-78' to each side of the equation.
78 + -78 + -3x = 18 + -78

Combine like terms: 78 + -78 = 0
0 + -3x = 18 + -78
-3x = 18 + -78

Combine like terms: 18 + -78 = -60
-3x = -60

Divide each side by '-3'.
x = 20

Simplifying
x = 20

See similar equations:

| 14+(9)+(-20)= | | 3n^2+6n=0 | | ln(7w+4)=6 | | 22+(-7)= | | 5.2-1.3x-1.5x=-0.4 | | 4.7-0.5x-0.3=-0.1 | | (7-z)(4z-2)=0 | | 2n+50+2n-10=180 | | Y=3sin^5(6x^2-7) | | x^2+6x=38 | | 9x-7=-7v | | 4(x-2)=-4x-32 | | 3x-0.75x-1.72=3.23 | | -w^5*(-7w^4)= | | 7x+50+95=180 | | 7-2k^2=-43 | | 3x-9y=44 | | (3z+2)(5+z)=0 | | -5u-24=-3(u+4) | | 4y(y+3)(y-7)=0 | | 7n(54)-9n=18 | | (8+z)(3z-4)=0 | | 5+4y=100 | | 4(y+3)(-y-8)=0 | | (2w+7)(5+w)=0 | | -16t^2+20t+8=0 | | (u+4)(u-1)=0 | | W^2+18w+c= | | (4x-36)+(2x+12)=180 | | (5+z)(3z-1)=0 | | x^4-2x^2=-20 | | 2w(w+7)(w-1)=0 |

Equations solver categories